Discrete dislocation dynamics simulations of twin size-effects in magnesium. Issue 1741 (12th February 2015) - Fan, Haidong; Aubry, Sylvie; Arsenlis, A.; El-Awady, Jaafar A.
ABSTRACT: A dislocation-{101̅2} twin boundary (TB) interaction model was proposed and introduced into discrete dislocation dynamics simulations to study the mechanical behavior of micro-twinned Mg. Strong strain hardening was captured by current simulations, which is associated with the strong TB's barrier effect. In addition, twin size effects with small TB spacing leading to a strong yield stress, were observed to be orientation dependent. Basal slip orientation produces a strong size effect, while prismatic slip does a weak one.